Answer:
-5 when ...
Explanation:
The rules of exponents can help you simplify the given product.
Rules
(a/b)^c = (a^c)/(b^c)
(ab)^c = (a^c)(b^c)
(a^b)(a^c) = a^(b+c)
(a^b)/(a^c) = a^(b-c)
Application
![\left((x)/(y)\right)^2(-x^2y)^3=\\\\(x^2(-1)^3(x^2)^3y^3)/(y^2)=-x^(2+2\cdot3)y^(3-2)=-x^8y](https://img.qammunity.org/2023/formulas/mathematics/high-school/b6u0nciwip2m4jm25v7ti039wslswp80ut.png)
This expression does not match any of those offered.
When x=-1 and y=5, this becomes ...
![-(-1)^8(5)=\boxed{-5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2sk95y9uehj4c5t58kg62cy2qqy7zb1skv.png)